1980
DOI: 10.3382/ps.0590737
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Vibration as an Aid in the Acetic Acid Method of Cleaning Eggs ,

Abstract: Experiments were conducted to evaluate the use of ultrasonic vibration as an aid to the dilute acid method of cleaning eggs. It is expected that ultrasonics could increase the efficiency of cleaning by reducing the length of time the eggs are exposed to the acid solution. To determine whether ultrasonics could be beneficial, penetration of the cleaning solution into the egg, shell thickness, shell cleanliness, interior quality, and microbial, organoleptic, and functional properties were measured.Shell penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The lack of effect of ultrasonication may have been due to the same reasons indicated above. Heath et al (1980) observed that ultrasonication did not enhance antibacterial effects of dipping eggs in 3% acetic acid.…”
Section: Resultsmentioning
confidence: 97%
“…The lack of effect of ultrasonication may have been due to the same reasons indicated above. Heath et al (1980) observed that ultrasonication did not enhance antibacterial effects of dipping eggs in 3% acetic acid.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, ultrasonic waves (ULT) have been investigated as a method of cleaning eggs and controlling pathogenic organisms (Dawson et al, 1962;Wladyka et al, 1963;Giarola et al, 1970;Sert et al, 2011;Aygun & Sert, 2012). Heath et al (1980) used a combination of ULT and acetic acid to clean eggs, and Slapp (1995) used a combination of ULT and a bactericide to sanitize hatching eggs. The mechanism of ULT cleaning is based on cavitation, a phenomenon produced in liquids when a ULT wave is travelling through them.…”
Section: Introductionmentioning
confidence: 99%